1988
DOI: 10.1007/bf01851203
|View full text |Cite
|
Sign up to set email alerts
|

A DIC-like picture on plasma and ascitic fluid of cirrhotic patients

Abstract: Ascitic fluid reinfusion in severe cirrhosis has frequently been associated with intravascular coagulation (DIC). A low-grade DIC has been postulated to be present in liver cirrhosis. PT, APTT, fibrinogen, plasminogen, antiplasmin, fibrin degradation producers (FDP), euglobulin lysis time, tissue plasminogen activator, and fibrinopeptide A were investigated both in the plasma and ascitic fluid of cirrhotic patients before and after the concentration-reinfusion technique. Our results indicate that increased thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…D-di-mer, a breakdown product of crosslinked fibrin, is a marker of ongoing fibrin turnover and represent an accurate marker of fibrinolytic activity (2). Previous studies have suggested the possible role of ascites in the pathogenesis of increased fibrinolysis associated with liver failure (3,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…D-di-mer, a breakdown product of crosslinked fibrin, is a marker of ongoing fibrin turnover and represent an accurate marker of fibrinolytic activity (2). Previous studies have suggested the possible role of ascites in the pathogenesis of increased fibrinolysis associated with liver failure (3,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…23 Ascites fluid reinfusion in severe cirrhosis has frequently been associated with disseminated intravascular coagulation. 24 Another intuitive finding by our method is that our model for arterial thrombosis identified affected arteries (hepatic artery, arterial occlusion); in contrast, our model for venous thromboembolism identified affected veins (portal vein thrombosis, left branch of portal vein). This finding demonstrates that our method can identify key vascular differences between these thrombotic phenotypes.…”
Section: Applying a Text-driven Approachmentioning
confidence: 80%